PENDAMPINGAN PENYUSUNAN RANCANGAN PEMBELAJARAN INOVATIF ABAD 21 PADA MAHASISWA - Agus Herianto; Sukuryadi Sukuryadi; Ibrahim Ibrahim; Mas’ad Mas’ad; Khosiah Khosiah; Mahsup Mahsup; Sintayana Muhardini; Irma Setiawan; Junaidin Junaidin; Zaenudin Zaenudin; Eka Fitriani; Najamudin Najamudin (SELAPARANG: Jurnal Pengabdian Masyarakat Berkemajuan, 2023)
ABSTRAKTujuan kegiatan pengabdian ini untuk meningkatkan pemahaman mahasiswa tentang model pembelajaran inovatif berorientasi konstruktivistik, karakteristik rancangan pembelajaran dan penyusunan rancangan pembelajaran inovatif abad 21. Metode kegiatan dengan tahapan terdiri dari persiapan, pelaksanaan dan evaluasi kegiatan. Hasil kegiatan pengabdian yaitu: 1) Mahasiswa peserta pengabdian memahami tentang model-model pembelajaran inovatif berorientasi konstruktivistik; 2) Mahasiswa peserta pengabdian memahami dengan baik cara mengimplementasikan model-model pembelajaran inovatif tersebut dalam kegiatan pembelajaran; 3) Mahasiswa peserta pengabdian memahami secara spesifik ciri atau karakteristik rancangan pembelajaran inovatif abad 21; 4) Mahasiswa peserta pengabdian memahami tentang penyusunan rancangan pembelajaran inovatif abad 21 dalam wujud RPP. Kata kunci: pendampingan; rancangan pembelajaran inovati abad 21; mahasiswa ABSTRACTThe purpose of this service activity is to increase students' understanding of constructivistic-oriented innovative learning models, characteristics of learning designs and the preparation of innovative learning designs of the 21st century. The method of activity with stages consists of preparation, implementation and evaluation of activities. The results of service activities are: 1) Students participating in the service understand about innovative learning models oriented to constructivism; 2) Students participating in the service understand well how to implement these innovative learning models in learning activities; 3) Students participating in the service understand specifically the characteristics or characteristics of innovative learning designs in the 21st century; 4) Students participating in the service understand about the preparation of innovative learning designs for the 21st century in the form of lesson plans. Keywords: mentoring; 21st century innovation learning design; student